Information literacy in Costa Rican universities. Visualization of the levels of incorporation from the information published in the websites of their libraries. - Uribe Tirado, Alejandro (2012)
Training in informational skills or Informational Literacy is one of the current challenges for libraries. In particular, if one considers the need to have criteria in view of the possibilities of access to enormous information resources, facilitated by digital media. University libraries have gradually incorporated this training, either through direct course programmes or the full revision of curricula through collaborative work with teachers and specialists from the different universities.At present, according to the information posted on the websites of the universities-IES of Costa Rica, a very small percentage of university libraries would be carrying out actions of levels 1 or 2 of incorporation to ALFIN. Most of them are still developing programs and processes focused on the traditional training of users, while another part, unfortunately, does not carry out any action-information from a training perspective.